A Procedure of Complete Averaging for Fuzzy Differential Inclusions on a Finite Segment - Plotnikov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We justify the applicability of the method of complete averaging on a finite segment for differential inclusions with fuzzy right-hand sides containing a small parameter.